Self Help Groups and Economic Development: Theories and Empirics - Chatterjee, Nilendu; Kundu, Dipak (Journal of Emerging Markets and Management, 2025)
Self-Help Groups (SHGs) have emerged as a significant mechanism for promoting financial inclusion and economic empowerment, particularly among women in developing economies. This study constructs a microeconomic comparative framework to evaluate the impact of SHG membership on financial inclusion and income generation. By contrasting two scenarios—individuals with SHG membership versus those without—we model savings, credit access, and investment behaviour through a utility maximization framework subject to budget constraints. The theoretical results demonstrate that SHG membership facilitates greater access to credit, incentivizes savings and investment, and ultimately leads to higher income levels. To validate the model's predictions with real-world scenarios, an econometric analysis is conducted using primary survey data from 600 households across two underdeveloped regions of West Bengal. The econometric findings corroborate the theoretical insights, affirming that SHG membership contributes positively to income enhancement and socio-economic inclusion. These results underscore the role of SHGs as instruments of inclusive development and financial empowerment.